COLLABORATIVE LEADERSHIP AND COMPETENCE AS PREDICTORS OF COLLABORATIVE BEHAVIOR AND PERFORMANCE AMONG EDUCATIONAL STAFF IN HIGHER EDUCATION: EVIDENCE FROM AN INDONESIAN PUBLIC UNIVERSITY - Yusna Yusuf; Saida Zainurossalamia ZA; Heni Rahayu Rahmawati (RADJA PUBLIKA, 2025)
This study investigates the impact of collaborative leadership and competence on employee performance, focusing on the mediating role of collaborative behavior among administrative civil servants at the Rectorate of Universitas Mulawarman, Indonesia. This study employs a quantitative explanatory design utilizing Partial Least Squares Structural Equation Modeling (SEM-PLS) with SmartPLS 4. Data were gathered from 168 respondents using a validated questionnaire assessing leadership, competence, collaboration, and performance indicators. The findings indicate that both collaborative leadership and competence exert significant positive effects on collaborative behavior, which, in turn, significantly enhances employee performance. Although collaborative leadership does not directly affect performance, it indirectly affects it through collaborative behavior, suggesting a full mediation pattern. Competence has both direct and indirect effects on performance, affirming that technical, digital, interpersonal, analytical, and adaptive competencies improve performance outcomes when manifested in collaborative action. This study contributes to the theoretical understanding by refining social exchange theory and competency-based human resource management within a behavioral collaboration framework. It identifies collaborative behavior as a central mechanism linking managerial capability and professional competence to institutional performance. The results offer practical implications for higher education governance, highlighting the importance of participatory decision-making, transparent information systems, and integrated competency development programs that promote interunit collaboration and enhance service quality.